LARVAE AND ADULTS OF ASCAROPS SP. (NEMATODA: SPIROCERCIDAE) COLLECTED FROM THE STOMACH OF MAXOMYS WHITEHEADI (RODENTIA: MURIDAE) IN KALIMANTAN, INDONESIA - Hideo Hasegawa; Kartika Dewi (Treubia, 2021)
Third-stage larvae and adults of spiruroid nematodes were found from the stomach wall and stomach lumen, respectively, of Maxomys whiteheadi (Rodentia: Murinae) captured in Bukit Soeharto, Kalimantan, Indonesia. Close observation using light microscope and scanning electron microscope (SEM) revealed that it belongs to the genus Ascarops (Nematoda: Spirocercidae), possibly to Ascarops strongylina (Rudolphi, 1819). It is presumed that this species is parasitic in wild boars, Sus barbatus, in the forest of Kalimantan, and utilizes the murine as a paratenic host, in which it usually remains as third larval stage but can occasionally develop to adult stage.